An MRI-trackable therapeutic nanovaccine preventing cancer liver metastasis. (July 2021) - Xiao, Bing; Li, Dongdong; Xu, Hongxia; Zhou, Xiaoxuan; Xu, Xiaodan; Qian, Yue; Yu, Feidan; Hu, Hongjie; Zhou, Zhuxian; Liu, Xiangrui; Gao, Jianqing; Slater, Nigel K.H.; et al.
Abstract: Cancer vaccines consisting of tumor-associated antigens (TAAs) can initiate a powerful antitumor immune response through antigen-presenting cells, such as dendritic cells (DCs) and macrophages, and have shown great potential in cancer prevention and therapy. However, poor anticancer efficacy and an uncertain immunization process have hitherto limited the application of cancer vaccines. Herein, a multifunctional nanovaccine comprising ovalbumin (OVA), MnO2, and polydopamine (OMPN) was prepared by a facile one-pot method. OMPN displayed excellent anticancer efficacy against an orthotopic melanoma and could also prevent liver metastasis in a tumor re-challenge mice model. Additionally, the migration behavior of DCs in the inguinal lymph node after vaccination was tracked by MRI contrasted with OMPN, indicating successful DC activation and immune response. The superior anticancer efficacy, especially the high efficiency against tumor metastasis, and the capability of tracking the immunization process make OMPN a very promising multifunctional nanovaccine for cancer therapy.